2017
DOI: 10.1111/ijfs.13501
|View full text |Cite
|
Sign up to set email alerts
|

Influences of pretreatment and drying methods on composition, micro/molecular structures and some health‐related functional characteristics of dietary fibre powder from orange pulp residues

Abstract: Summary Influences of pretreatment methods (washing, blanching, soaking in ethanol), drying methods (hot air‐drying, infrared‐drying, microwave‐drying) and drying temperature on selected characteristics of dietary fibre powder from orange pulp residues were investigated. Pretreatments improved the hydration properties, oil‐holding capacity and glucose dialysis retardation index, but led to losses of fibres, decreased α‐amylase inhibitory activity and aflatoxin B1 adsorption capacity. Hydration properties, oil‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Overwhelming epidemiological and clinical investigations have repeatedly shown the apparent association between high fruit intake and the decreased incidence of cardiovascular and other chronic diseases (Borbal an, Zorro, Guill en, & Barroso, 2003;Kris-Etherton et al, 2002). Natural antioxidants such as vitamins, carotenes, minerals, or fiber are not supposed to be the only components responsible for the antioxidant properties of fruit (Chuyen, Roach, Golding, Parks, & Nguyen, 2017;Sungsinchai, Niamnuy, Jaree, & Devahasti, 2017). In previous research, the significant correlations have been reported between phenolic contents and antioxidant capacities (Su et al, 2017;Zhuang, Ma, Guo, & Sun, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Overwhelming epidemiological and clinical investigations have repeatedly shown the apparent association between high fruit intake and the decreased incidence of cardiovascular and other chronic diseases (Borbal an, Zorro, Guill en, & Barroso, 2003;Kris-Etherton et al, 2002). Natural antioxidants such as vitamins, carotenes, minerals, or fiber are not supposed to be the only components responsible for the antioxidant properties of fruit (Chuyen, Roach, Golding, Parks, & Nguyen, 2017;Sungsinchai, Niamnuy, Jaree, & Devahasti, 2017). In previous research, the significant correlations have been reported between phenolic contents and antioxidant capacities (Su et al, 2017;Zhuang, Ma, Guo, & Sun, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Microwave drying (MD) is a relatively inexpensive method in which dipole heating causes water to migrate toward the product surface (Salimi Hizaji, Maghsoudlou, & Jafari, ). A higher drying rate is expected for the MD process compared to other drying processes because microwave energy can rapidly penetrate the inner layer of a dried sample (Sungsinchai, Niamnuy, Jaree, & Devahastin, ). The absorbed energy is then converted into heat, causing a rapid temperature increase and hence an accelerated drying rate (Therdthai & Zhoui, ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher agglomeration and a less dense fibre network reduce the WRC and subsequent rheological properties. Agarwal et al (2018), 29 Sungsinchai et al (2017) 23 and Eyholzer et al (2010) 38 have found that the WRC is inversely proportional to the fibre aggregation that occurs during the drying processes such as oven drying and vacuum drying. 38…”
Section: Resultsmentioning
confidence: 99%
“…1,4,19 The pre-treatment conditions of the citrus fibres are important for controlling their size, shape, composition, and functionality. 23 Pre-treatment involves a process flow of acid hydrolysis, bleaching, washing, filtration, and drying. 18 The process of acid hydrolysis starts with breaking the glycosidic linkages within the amorphous regions since solvents such as water and acid penetrate the amorphous regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation